EXPERIMENTAL INSIGHTS INTO PHOTOVOLTAIC POWER GENERATION FOR SUSTAINABLE ENERGY SOLUTIONS - Kamal Yogi (American Journal Of Agriculture And Horticulture Innovations, 2024)
This study provides experimental insights into photovoltaic (PV) power generation as a sustainable energy solution. Photovoltaic technology has emerged as a pivotal renewable energy source, offering significant potential for clean and efficient electricity generation. The research explores the performance and efficiency of PV systems through experimental data analysis, focusing on factors such as solar irradiance, module characteristics, and energy output. By evaluating the practical application of PV technology in varying environmental conditions, the study aims to contribute valuable insights into its role in achieving sustainable energy solutions and addressing global energy challenges.